Exploring Sex Differences in the Neural Correlates of Self-and Other-Referential Gender Stereotyping - Hornung, Jonas; Smith, Elke; Junger, Jessica; Pauly, Katharina; Habel, Ute; Derntl, Birgit (Frontiers in Behavioral Neuroscience, 2019)
While general self-referential processes and their neural underpinnings have been extensively investigated with neuroimaging tools, limited data is available on sex differences regarding self- and other-referential processing. To fill this gap, we measured 17 healthy women and men who performed a self- vs. other-appraisal task during functional magnetic resonance imaging (fMRI) using gender-stereotypical adjectives. During the self-appraisal task, typical male (e.g. ‘dominant’, ‘competitive’) and female adjectives (e.g. ‘communicative’, ‘sensitive’) were presented and participants were asked whether these adjectives applied to themselves. During the other-appraisal task, a prototypical male (Brad Pitt) and female actor (Julia Roberts) was presented and participants were asked again to judge whether typical male and female adjectives applied to these actors. Regarding self-referential processes, women ascribed significantly more female compared to male traits to themselves. At the same time both women and men indicated a stronger desire to exhibit male over female traits. While fMRI did not detect general sex differences in the self- and other-conditions, some subtle differences were revealed between the sexes: both in right putamen and bilateral amygdala stronger gender-congruent activation was found which was however not associated with behavioral measures like the number of self-ascribed female or male attributes. Furthermore, sex hormone levels showed some associations with brain activation pointing to a different pattern in women and men. Finally, the self- vs. other-condition in general led to stronger activation of the anterior cingulate cortex while the other- vs. self-condition activated the right precuneus more strongly which is in line with previous findings. To conclude, our data lend support for subtle sex differences during processing of stereotypical gender attributes. However, it remains unclear whether such differences have a behavioral relevance. We also point to several limitations of this study including the small sample size and the lack of control for potentially different hormonal states in women.